A Brief Overview on Ferrite (Fe3O4) Based Polymeric Nanocomposites: Recent Developments and Challenges (Journal of Research Updates in Polymer Science, 2015)
In this article, we have mainly discussed about ferrite (Fe3O4) and its polymer based nanocomposites. Ferrite particles have become an important research material because of their vast applications in the field of biotechnology, magnetic resonance imaging (MRI), and data storage. It has been observed that ferrite Fe3O4 particles show best performance for size less than 10-30 nm. This happens due to the super paramagnetic nature of such particles. In super paramagnetic range these particles exhibit zero remanence or coercivity. Therefore, various properties of ferrite (Fe3O4) nanoparticles and its polymer nanocomposites are very much dependent on the size, and distribution of the particles in the polymeric matrix. Moreover, it has been also observed that the shape of the nanocrystals plays important role in the determination of their fundamental properties. These particles show instability over longer times due to the formation of agglomerates generated by high surface energies. Therefore, protection strategies such as grafting and coatings with silica/carbon or polymers have been developed to stabilize them chemically. Recently, silylation technique is mainly used for the modification of nanoparticles. Experimentally, it has been observed that nanocomposites composed of polymer matrices and ferrite showed substantial improvements in stiffness, fracture toughness, sensing ability (magnetic as well as electric), impact energy absorption, and electro-catalytic activities to bio-species.